Niveles de harina de banano y carragenato semi industrial en la formulación de mortadela de pollo Mocache 2014. - Ochoa Daza, Jorge Omar (2014)
This research was carried in experimental farm "La María" State Technical University of Quevedo, in Workshop Meat, Faculty of Animal Science, located at Km 7 via Quevedo - El Empalme, in the Province of Los Rios, whose geographical coordinates are: 79 ° 27 'west longitude and 01 ° 06' south latitude, at a height of 73 meters. The objectives of this research are Evaluate different levels of banana flour (2%, 4% and 6%) and semi-industrial carrageenan (0.1% and 2%) in the formulation of chicken mortadella to determine the physical, chemical , microbiological and organoleptic characteristics of the final product and raise the profit economic indicator - cost in the development of bologna to assess profitability. A completely randomized design with 4 replications bivariate accordance with applied. 3 percentage banana flour (2, 4, and 6%) and semi-industrial carrageenan (0.1, 0.15 and 2%) were used in the formulation of chicken mortadella, experiencing a total of six interactions front of a witness. Test Tukey multiple ranges probability 0.05 was used for comparison between the average. For treatments profitability ratio was used Benefit - Cost and organoleptic variables was determined by means of KruskalWallis. In all bromatological variables there was significant when comparing the witness vs all statistical difference. The best feature was obtained by treatment T4. The results showed that if organoleptic difference existed between the average parameters resulting odor, color and texture. As for microbiological analyzes will be conducted to better treatment based on the organoleptic, which was the T4, resulting in low contamination due to good hygiene applied during processing. Most performance was achieved with treatment T4 with 4% Banana Flour and 0.2% carrageenan